Overview of the predictive value of quantitative 18 FDG PET in head and neck cancer treated with chemoradiotherapy. (December 2016) - Castelli, J.; De Bari, B.; Depeursinge, A.; Simon, A.; Devillers, A.; Roman Jimenez, G.; Prior, J.; Ozsahin, M.; de Crevoisier, R.; Bourhis, J.
Highlights: SUVMax is a poor predictive parameter when compared with volumetric parameters (MTV, TLG). MTV and/or TLG pre-treatment are well correlated with clinical outcome. MTV had a better predictive value than GTV and/or AJCC staging. Abstract: 18 F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) allows to quantify the metabolic activity of a tumor (glycolysis) and has become a reference tool in oncology for the staging, restaging, radiotherapy planning and monitoring response in many cancers. Quantitative analyses have been introduced in order to overcome some of the limits of the visual methods, allowing an easier and more objective comparison of the inter- and intra-patients variations. The aims of this review were to report available evidences on the clinical value of quantitative PET/CT parameters in HNC. Forty-five studies, for a total of 2928 patients, were analyzed. Most of the data available dealt with the intensity of the metabolism, calculated from the Standard Uptake Value (SUV). Metabolic Tumor Volume (MTV) was well correlated with overall survival and disease free survival, with a higher predictive value than the maximum SUV. Spatial distribution of metabolism and textural analyses seems promising.